1999
DOI: 10.1021/bi9913855
|View full text |Cite
|
Sign up to set email alerts
|

Haloalkane Dehalogenases:  Structure of aRhodococcusEnzyme,

Abstract: The hydrolytic haloalkane dehalogenases are promising bioremediation and biocatalytic agents. Two general classes of dehalogenases have been reported from Xanthobacter and Rhodococcus. While these enzymes share 30% amino acid sequence identity, they have significantly different substrate specificities and halide-binding properties. We report the 1.5 A resolution crystal structure of the Rhodococcus dehalogenase at pH 5.5, pH 7.0, and pH 5.5 in the presence of NaI. The Rhodococcus and Xanthobacter enzymes have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
182
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(191 citation statements)
references
References 42 publications
(51 reference statements)
7
182
0
Order By: Relevance
“…DhaA dehalogenated mono-and dibrominated propanes with a catalytic efficiency similar to that of DhlA, whereas the catalytic efficiency of DhaA on 1,2,3-tribromopropane was ∼30-fold higher (25,26). This observation is consistent with the larger active site cavity of DhaA that can probably better accommodate large bulky substrates such as 1,2,3-tribromopropane (13). DhaA dehalogenated the different chlorinated propanes with considerable differences in maximum turnover as well as affinity.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…DhaA dehalogenated mono-and dibrominated propanes with a catalytic efficiency similar to that of DhlA, whereas the catalytic efficiency of DhaA on 1,2,3-tribromopropane was ∼30-fold higher (25,26). This observation is consistent with the larger active site cavity of DhaA that can probably better accommodate large bulky substrates such as 1,2,3-tribromopropane (13). DhaA dehalogenated the different chlorinated propanes with considerable differences in maximum turnover as well as affinity.…”
Section: Resultssupporting
confidence: 78%
“…Compared to DhlA, the active site of DhaA is connected to the solvent by a much larger tunnel and is less buried in the protein core (12). In addition, Newman et al suggested that at pH 7-9, where the enzyme activity is measured, the cap domain of DhaA becomes more flexible (13). These observations suggest that the accessibility of water to the active site may be facilitated, allowing a faster exchange of the halide ions and water with the bulk solvent.…”
Section: Transient-state Kinetic Analysis Of 13-dibromopropane Convementioning
confidence: 99%
“…The haloalkane dehalogenases that degrade these compounds are homologous to the classical enzyme from Xanthobacter autotrophicus [3]. Even though sequence similarities are low, the overall structures are very similar and the catalytic residues are conserved [4]. Another example of a recently studied hydrolytic dehalogenase is LinB from Sphingomonas paucimobilis; this enzyme is involved in the conversion of tetrachlorocyclohexadiene, an intermediate in the γ-hexachlorocyclohexane degradation pathway ( Figure 1) [5].…”
Section: Aerobic Growth On Halogenated Aliphatic Compoundsmentioning
confidence: 99%
“…The enzymes possess a catalytic triad formed by residues of the main domain, with an aspartate as the nucleophile that displaces the halogen from the substrate. In addition, these enzymes have a conserved tryptophan residue in the main domain and variable residues (phenylalanine or asparagine) in the cap domain that contribute to halide binding [4,5].…”
Section: Aerobic Growth On Halogenated Aliphatic Compoundsmentioning
confidence: 99%
“…The "static" structural determinants of the substrate specificity were implied from the crystallographic analysis of three dehalogenases belonging to different specificity classes, that is, Xanthobacter autotrophicus GJ10 (DhlA; Verschueren et al 1993b), Rhodococcus sp. (DhaA; Newman et al 1999), and Sphingomonas paucimobilis UT26 (LinB; Marek et al 2000). The substrate specificity appears to be modulated not only by the size and shape of the active site but also by the position and shape of tunnels connecting buried active sites with a bulk solvent (Damborsky and Koca 1999).…”
mentioning
confidence: 99%